MAKNA ESKATOLOGI DALAM SEVENTH DAY ADVENTIST HYMNAL (ANALISIS SEMIOTIKA) - KEMBUAN, MIREILLE YOLANNIE THESSA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTThis research which is entitled ?Makna Eskatologi dalam Seventh Day Adventist Hymnal? is focused on sign and meaning that can be found in Seventh Day Adventist Hymnal. The aims of this research are to identify, classify and analyze the signifier, signified and the meaning of eschatology that can be found in lyrics on Seventh Day Adventist Hymnal. The writer uses theory of Saussure to identify and classifythe data. In analyzying the data, the writer used the theory of Pierce which states that An interpretant (or interpretant sign) is the sign's more or less clarified meaning or ramification, a kind of form or idea of the difference which the sign's being true or undeceptive would make. The source of lyrics songs was taken from the book of Seventh Day Adventist Hymnal. The method of this research is qualitative method. Qualitative data is a form of words rather than a row of numbers. The results of this research show that based on the theory of Saussure there is signifier and signified in lyrics songs are on SDA Hymnal and based on the theory of Pierce there are 7 clauses,17 phrases, 16 sentences and 3 words that have eschatology meaning which consists of Jerusalem; my happy home, Marching to Zion, Sweet by and by, Jerusalem the Golden, Joy by and by, Shall we gather at the river, The homeland, I?m going home, There?ll be no sorrow there, Beautiful Zion, Together let us sweetly live, In the garden, How lovely is thy dwelling place, In a little while we?re going home, Over yonder, Burdens are lifted at Calvary, The Lord is coming, Gleams of the golden morning, You will see your Lord a-coming, Don?t you see my Jesus coming, Nearer my God to thee, O God; unseen, yet ever near, Christ is coming, Hail him the king of glory, Come; thou long expected Jesus, It may be at morn, There?ll be no dark valley, That glorious day is coming, Tis almost time for the Lord to come, Jesus is coming again, We have this hope, When Jesus comes in glory, We know not the hour, O brother; be faithful, The king shall come, Christ the Lord; all power possessing, The judgment has set, O solemn thought, Day of the judgment; day of wonders!, Once to every man and nation._________________Keywords: Eschatology Meaning, Seventh Day Adventist Hymnal, Semiotic Analysis